Novel Means for Photoprotection - Sondenheimer, Kevin; Krutmann, Jean (Frontiers in Medicine, 2018)
Due to changes in human lifestyle (expanded sunbathing, the use of solaria, etc.) and, most importantly, increasing lifetime and thus higher cumulative exposure to solar radiation, skin aging and skin cancer have become major health issues. As a consequence effective photoprotection is of outmost importance to humans. In this regard a lot has been learned in the past about the cellular and molecular basis underlying ultraviolet (UV) radiation-induced skin damage and, based on this knowledge, numerous skin protective approaches including organic and inorganic UV-filters, but also topically applicable antioxidants, DNA repair enzymes and compatible solutes as well as oral photoprotective strategies based on nutritional supplements have been developed. A new aspect is here that sun protection of human skin might even be possible after solar radiation-induced skin damage has occurred. A second, very important development was prompted by the discovery that also wavelengths beyond the UV spectrum can damage human skin. These include the blue light region of visible light (VIS) as well as the near infrared range (IRA) and corresponding sunprotection strategies have thus recently been or are still being developed. In this article we will provide a state of the art summary of these two novel developments and, at the end, we will also critically discuss strengths and weaknesses of the current attempts, which mainly focus on the prevention of skin damage by selected wavelengths but greatly ignore the possibility that wavelengths might interfere with each other. Such combined effects, however, need to be taken into account if photoprotection of human skin is intended to be global in nature.